2020
DOI: 10.1021/acs.cgd.0c00911
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Efficient Discovery of Cocrystals via a Network-Based Recommendation Model

Abstract: Experimental screening of cocrystals is usually laborious and time-consuming; therefore, it is urgent to develop effective in silico predictive models to guide cocrystal discovery. In this study, network-based recommendation models were proposed to predict new cocrystals for molecules in cocrystal network. The local random walk (LRW) recommender algorithm was first confirmed as an effective model in cocrystal design. The algorithmic principle of LRW could capture the supramolecular synthon mechanisms in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…According to this criterion, the predictive capability of SMINBR was further compared with HBP, HBC, HBE, and LRW by conducting diclofenac and nevirapine cocrystal prediction tasks. 28,37 The detailed predictive results are provided in Tables S7 and S8 in the Supporting Information, and these results are summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to this criterion, the predictive capability of SMINBR was further compared with HBP, HBC, HBE, and LRW by conducting diclofenac and nevirapine cocrystal prediction tasks. 28,37 The detailed predictive results are provided in Tables S7 and S8 in the Supporting Information, and these results are summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Top 10 interaction partners for APA were recommended (Table 4), in which fumaric acid, succinic acid, adipic acid, oxalic acid, benzoic acid, malonic acid, glutaric acid, 4-aminobenzoic acid, and 4-hydroxybenzoic acid have been found to form cocrystals with APA in previous studies. 28,42 In this study, paradioxybenzene (PDB) was subject to experimental screening and found to form a new cocrystal with APA. This new APA-PDB cocrystal was analyzed by powder X-ray diffraction (PXRD) to distinguish it from the parent phases (see Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the selection of coforms has still largely relied on trial and error, which is time consuming and labor-intensive. Recently, a variety of computer-assisted approaches have emerging as attractive tools to accelerate the screening process of cocrystals 214 , 215 , 216 , 217 , 218 . For example, the artificial neural network models are developed to predict cocrystal formation by analyzing a network of coformers extracted from the Cambridge Structural Database (CSD) 218 .…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%